Chlamydia, Gonorrhea, and Human Immunodeficiency Virus Infection Among Transgender Women and Transgender Men Attending Clinics that Provide Sexually Transmitted Disease Services in Six US Cities: Results From the Sexually Transmitted Disease Surveillance Network. Issue 2 (February 2019) - Pitasi, Marc A.; Kerani, Roxanne P.; Kohn, Robert; Murphy, Ryan D.; Pathela, Preeti; Schumacher, Christina M.; Tabidze, Irina; Llata, Eloisa
Abstract : Background: Transgender women and transgender men are disproportionately affected by human immunodeficiency virus (HIV) infection and may be vulnerable to other sexually transmitted diseases (STDs), but the lack of surveillance data inclusive of gender identity hinders prevention and intervention strategies. Methods: We analyzed data from 506 transgender women (1045 total visits) and 120 transgender men (209 total visits) who attended 26 publicly funded clinics that provide STD services in 6 US cities during a 3.5-year observation period. We used clinical and laboratory data to examine the proportion of transgender women and transgender men who tested positive for urogenital and extragenital chlamydial or gonococcal infections and who self-reported or tested positive for HIV infection during the observation period. Results: Of the transgender women tested, 13.1% tested positive for chlamydia and 12.6% tested positive for gonorrhea at 1 or more anatomic sites, and 14.2% were HIV-infected. Of transgender men tested, 7.7% and 10.5% tested positive for chlamydia and gonorrhea at 1 or more anatomic sites, and 8.3% were HIV-infected. Most transgender women (86.0% and 80.9%, respectively) and more than a quarter of transgender men (28.6% and 28.6%, respectively) with an extragenital chlamydial or gonococcal infection had a negative urogenital test at the same visit. Conclusions: Publicly funded clinics providing STD services are likely an important source of STD care for transgender persons. More data are needed to understand the most effective screening approaches for urogenital, rectal, and pharyngeal Chlamydia trachomatis and Neisseria gonorrhoeae infections in transgender populations. Abstract : Supplemental digital content is available in the text.This analysis of clinic-based surveillance data provides estimates of laboratory-confirmed urogenital, rectal, and pharyngeal chlamydial and gonococcal infection and self-reported and laboratory-confirmed human immunodeficiency virus infection among transgender women and transgender men.